PENGARUH SISTEM AKUNTANSI MANAJEMEN BROAD SCOPE DAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERATING PADA PENGARUH PARTISIPASI PENGANGGARAN TERHADAP KESENJANGAN ANGGARAN - ARYA PRADIPTA (Media Bisnis, 2013)
This research examines the moderating effect of management accounting system broadscope and organization commitment on the relationship between the budget participation and budgetary slack. Eighty nine business unit managers from manufacturing industry in Jakarta, Bogor, Tangerang and Karawang had participated in this research. The collecting data used a questionnaire survey via contct person, electronicmail, inter-views and post. Data were analyzed using two-way analysis of variance. The results showed that the effects of the budget participation and budgetary slack were not dependent on the management accounting system broadscope and organization commitment.